Determinants of low birth weight and its relationship with stunted toddler status in Magelang Regency, Indonesia - Giyarsih Sri Rum (EDP Sciences, 2021)
Stunting contributes to a decrease in the quality of life. One of the potential factors which causes stunting is low birth weight (LBW). The objectives of this study are (1) to obtain representations of the characteristics of mothers and stunted toddlers; (2) to analyze the influence of maternal age at birth, gestational age, maternal hygiene and health behavior, and maternal nutrition knowledge related to LBW; and (3) to identify the relationship between LBW and stunted toddlers in Magelang Regency. This study used a mix-method approach that combined primary data and in-depth interviews. The binary logistic regression results found that maternal age at birth, gestational age, maternal hygiene and health behavior, and maternal nutritional knowledge had a significant effect to LBW on stunted toddlers.